Cash Waqf-Based Community Empowerment in Indonesia: An Islamic Social Finance Perspective - M. Hidayat Ediz; Nur Rasyidah Kamaruzaman; Yosi Aryanti (ZAWA: Management of Zakat and Waqf Journal, 2026)
Cash waqf is a strategic instrument of Islamic social finance with considerable potential to promote community empowerment and enhance social welfare in Indonesia. This study aims to analyze the role of cash waqf in community empowerment through its management mechanism and implementation across various sectors. This study employed a qualitative method using a content analysis approach to examine laws and regulations, scholarly literature, and relevant documents on cash waqf in Indonesia. The findings indicate that cash waqf is managed through Islamic Financial Institutions Receiving Cash Waqf (LKS-PWU), while nazhirs are responsible for developing waqf funds productively without reducing their principal value. The returns generated from the management of cash waqf are allocated to community empowerment initiatives in the education, healthcare, social, and economic sectors, including qard al-hasan-based financing for microenterprises. The study implies that strengthening the governance of cash waqf and enhancing collaboration between nazhirs and Islamic financial institutions can maximize the contribution of cash waqf to sustainable community empowerment and social welfare in Indonesia.